Pengaruh Tanaman Enceng Gondok Terhadap Aktivitas Perekonomian Masyarakat Desa Kebondowo di Rawa Pening - Dila Fitriani; Rose Ana Anggun Fajariah; Robiatul A’dawiyah; Ibnu Aris Abdullah; Ulfatun Khasanah; Ramadhani Rizky; Mutiara Ilmi (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
Eichhornia crassipes is one of the sources of income for the community arround Rawa Pening and have a high economic value in the form of crafts. The purpose of this research was to determine the type of utilization of Eichhornia crassipes in Rawa Pening and the impact of Eichhornia crassipes on the economy of the people in Kebondowo Village. This type of research is quantitative descriptive using the method of observation and interviews. The result of this research showed that the Eichhornia crassipes growing in Rawa Pening had an impact on the economic activities of the surrounding communities with various types of utilization like seeker, collectors, weaver, and craftsmen Eichhornia crassipes.